An unusual case of neurobrucellosis presenting as demyelination disorder - Bektaş, Ömer; Özdemir, Halil; Yılmaz, Arzu; Fitöz, Suat; Çiftçi, Ergin; İnce, Erdal; Aksoy, Erhan; Deda, Gülhis (The Turkish Journal of Pediatrics, 2013)
Brucellosis is a public health problem in most countries in the Mediterranean. Involvement of the central nervous system is seen in 4-13% of patients with brucellosis. A 13-year-old girl was admitted because of gait disturbance, diplopia, and dizziness. Her complaints began about 1.5 years ago. The second symptomatic episode repeated about three months ago and the third two months ago. In total, attacks repeated 3 times over 1.5 years. The magnetic resonance imaging (MRI) and the clinical features mimicked multiple sclerosis. The patient was given pulse steroid treatments. After steroid treatment, her gait disturbance and diplopia improved over the short term. Following positive developments, her symptoms recurred. The tests were repeated; the MRI showed increasingly high signal abnormalities, and Brucella melitensis was grown in cerebrospinal fluid. The patient was started on an oral combination of rifampin, doxycycline, and ciprofloxacin. MRI findings improved markedly after nine months of treatment. Although neurobrucellosis is associated rarely with demyelination in adults, this finding has not been reported previously in children or adolescents. Additionally, this case is the first in terms of involvement of the corpus callosum in neurobrucellosis. In this article, we present an unusual case of neurobrucellosis.